Assessing DOC export from a Sphagnum‐dominated peatland using δ13C and δ18O–H2O stable isotopes. Issue 21 (1st August 2019) - Buzek, Frantisek; Novak, Martin; Cejkova, Bohuslava; Jackova, Ivana; Curik, Jan; Veselovsky, Frantisek; Stepanova, Marketa; Prechova, Eva; Bohdalkova, Leona
Abstract: Dissolved organic carbon (DOC) originating in peatlands can be mineralized to carbon dioxide (CO2 ) and methane (CH4 ), two potent greenhouse gases. Knowledge of the dynamics of DOC export via run‐off is needed for a more robust quantification of C cycling in peatland ecosystems, a prerequisite for realistic predictions of future climate change. We studied dispersion pathways of DOC in a mountain‐top peat bog in the Czech Republic (Central Europe), using a dual isotope approach. Although δ 13 CDOC values made it possible to link exported DOC with its within‐bog source, δ 18 OH2O values of precipitation and run‐off helped to understand run‐off generation. Our 2‐year DOC–H2 O isotope monitoring was complemented by a laboratory peat incubation study generating an experimental time series of δ 13 CDOC values. DOC concentrations in run‐off during high‐flow periods were 20–30 mg L −1 . The top 2 cm of the peat profile, composed of decaying green moss, contained isotopically lighter C than deeper peat, and this isotopically light C was present in run‐off in high‐flow periods. In contrast, baseflow contained only 2–10 mg DOC L −1, and its more variable C isotope composition intermittently fingerprinted deeper peat. DOC in run‐off occasionally contained isotopically extremely light C whose source in solid peat substrate was not identified. Pre‐event water made up on average 60% of the water run‐off flux, whereas direct precipitation contributed 40%. Run‐off response to precipitation was relatively fast. A highly leached horizon was identified in shallow catotelm. This peat layer was likely affected by a lateral influx of precipitation. Within 36 days of laboratory incubation, isotopically heavy DOC that had been initially released from the peat was replaced by isotopically lighter DOC, whose δ 13 C values converged to the solid substrate and natural run‐off. We suggest that δ 13 C systematics can be useful in identification of vertically stratified within‐bog DOC sources for peatland run‐off. Abstract : High precipitation results in a high discharge from the peat bog with elevated DOC originating from fresh peat on the top; production of new DOC increases with temperature. DOC in baseflow originates from various depths along the vertical peat profile.